Development model of literacy tourism through architectural design and library service integration - Diah Sri Rejeki; Sayed Muhammad Aiman Sayed Abul Khair; Haria Saputry Wahyuni; Merryam Agustine; Sari Nurvita Rianti; Erika Nurmayanti (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. The Museum of the Asian-African Conference, through its Literacy Festival, presents innovative library services that integrate educational, historical, and architectural elements into a unified visitor experience. This study aims to implement a literacy tourism development model that integrate architectural design and library services offering a new approach to strengthening immersive and contextual literacy learning. Research Methods. A qualitative case study approach was applied, with data collected through participatory observation, in-depth interviews, and visual documentation during the festival. Data Analysis. Thematic analysis was used to analyse the data with several steps such as data reduction, categorization, and narrative interpretation to explore the interaction between space and services. Results. The narrative architectural design, featuring chronological spatial layouts, thematic lighting, and quotations from world figures, evoked emotional and cognitive responses from visitors. Library services including exhibitions, workshops, and book discussions encouraged cross-generational engagement and strengthened historical literacy. Conclusion. The integration of colonial architecture and participatory library services creates an immersive literacy tourism model that combines cognitive, emotional, and cultural learning. This study offers an interdisciplinary perspective that positions architecture as a narrative medium within library services, providing practical insights for libraries and museums in developing experience-based literacy programs.